Portrait of women workers of apple orchards: A study on the "triple role" and "family decision making role" of women workers of an apple orchard in Poncokusumo District, Malang Regency - Budhy Prianto; Alifiulahtin Utaminingsih (Jurnal Penelitian, 2005)
This study aims, firstly, to obtain an overview of the role or responsibility of household work by the family, especially the husband, which is imposed on female workers in the Poncokusumo apple orchard. Second, to get an idea of the role of women workers of an apple orchard in Poncokusumo in the family decision-making process. This research is a case study that uses a survey method with a qualitative descriptive approach with a women's perspective. Questionnaires were distributed to 40 women (housewives) apple orchard workers as a sample determined by the quota. Data analysis used the Harvard method or the Gender Framework Analysis-GFA method. Some research findings that can be put forward are first, that the productive role of women in Poncokusumo apple orchards is very high, while the domestic and/or reproductive role is high, and the role of the public is also high. Further research findings also show that women workers apple orchard in Poncokusumo also has a high role in the decision-making process at the family level.